Water and cognition in early modern English literature
1 online resource (314 pages)
Keywords: Water and cognition seem unrelated things, the one a physical environment and the other an intellectual process. The essays in this book show how bringing these two modes together revitalizes our understanding of both. Water and especially oceanic spaces have been central to recent trends in the environmental humanities and premodern ecocriticism. Cognition, including ideas about the "extended mind" and distributed cognition, has also been important in early modern literary and cultural studies over the past few decades. This book aims to think "water" and "cognition" as distinct critical modes and also to combine them in what we term "watery thinking." Water and Cognition brings together cognitive science and ecocriticism to ask how the environment influences how humans think, and how they think about thinking. The collection explores how water - as element, as environment, and as part of our bodies - affects the way early modern and contemporary discourses understand cognition.